Towards a 21st century university: Teachings from consumer behaviour applicable to higher education - du Preez, Ronel (South African Journal of Higher Education, 2016)
The South African Higher Education landscape has changed dramatically over the last 25 years. The purpose of this conceptual article is to challenge higher education institutions to learn/draw from a wider spectrum of knowledge domains in their quest toward a 21st century university. The author argues that the rich body of theoretical knowledge which is contained in the domain of consumer psychology can contribute generously to the understanding of the behaviour of a principle stakeholder, namely the student. Four teachings include, firstly, develop and manage your corporate and brand image, secondly, determine the valence of decision-making criteria and market accordingly; thirdly, research your consumer target market and finally attend to consumer needs. Five challenges are presented to higher education institutions (specifically universities) in South Africa and recommendations for future research are made.